Variations in carbon burial and sediment accretion along a tidal creek in a Florida salt marsh. (15th September 2017) - Arriola, Jill M.; Cable, Jaye E.
Abstract: Salt marshes store large quantities of carbon in the form of buried organic matter (OM) and consequently play a major role in the global carbon cycle, yet vertical accretion and carbon burial rates (CBRs) can vary by orders of magnitude on small spatial scales. The goal of this study was to provide insight into carbon burial variability of a single tidal salt marsh. Six marsh sediment cores were collected along a tidal creek in the Big Bend of Florida from the mouth to the coastal forest within the marsh levee and plain. Each was analyzed for porosity, % OM, total organic carbon (TOC), total nitrogen (TN), δ 13 C, δ 15 N, and excess 210 Pb to determine vertical accretion and CBRs. Porosity, % OM, and TOC and TN were found to be highest in the low marsh and within the marsh levee. Stable isotopes of OM indicate the source is dominated by C3 plant species in both the levee and plain. Average vertical accretion ranges from 0.9 mm yr −1 to 2.2 mm yr −1 with the slowest rates in the low marsh. Average carbon burial ranges from 49.5 g OC m −2 yr −1 to 109.5 g OC m −2 yr −1 . High carbon burial associated with low sediment accumulation in the Low Marsh and low carbon burial associated with high sediment accumulation rates in the High Marsh are typical in this marsh. These variations imply that the highest carbon burial occurs in the zone most vulnerable to loss via inundation and erosion.